A Study of Mathematical Misconception About the Geometry of 2nd Year Students in Mathematics, Faculty of Education Nakhonsawan Rajabhat University - Kitthao, Kwanchanok; Chummuengyen, Irene (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2022)
This research aimed to study 1) compare the mean between male and female students of the geometric concept test results 2) study the misconceptions about the geometry classified by content issue and 3) study the misconceptions about the geometry classified by misconceptions characters. This is a quantitative research and study population was 32 second-year mathematics students. Using the geometric concept test, 30 items were used with the following topics: relational dimensions, parallelism, geometry, angles, line segments, midpoints, distances, slopes, circles, ellipses, parabola and hyperbola. Data analysis by percentage and average number of students who answered incorrectly in each item of the geometric concept test. The research results were found as follows; 1) misconceptions about the geometry that male students more than female students were angles, distances, circles and parabolas. Misconceptions about the geometry that female students more than male students were relational dimensions, geometry, slope, ellipse, and hyperbola. The content that students had the most misconceptions about was distance and angle accounted for 79 percent of all students 2) students will have the most misconceptions about the conical section, accounted for 73.38% and 3) male and female students misconceptions about the geometry classified by misconceptions characters in terms of applying rules/theories to apply more than definitions and theories.